Volatile phytoconstituent profile of Argemone mexicana L. Leaves and pharmacological importance - CHILIVERY RAVI KIRAN; SANGILIMUTHU ALAGAR; SOWMYA PRIYA MANOHARAN (International Journal of Pharma and Bio Sciences, 2017)
The current study was performed to identify the bioactive compounds from methanol extract of Argemone mexicana leaves by Gas Chromatography and Mass Spectrum (GC-MS) analysis and to review their medicinal applications to mankind. The Argemone mexicana leaves extract was prepared with methanol and analyzed by GC-MS using Perkin Elmer Elite on 5 capillary column. Total 22 compounds were identified by GC-MS analysis and cycloserine, 2-Methoxy-4-vinylphenol, 5-hydroxymethyl 2-furfural, D-Allose, 3-Deoxy-d-mannoic lactone, Palmitic acid and Tetradecanoic being the major compounds with good medicinal applications as an antibiotic to treat multidrug resistant tuberculosis, antiseptic, treating anxiety disorders, chronic schizophrenic patients, antimicrobial, antioxidant, antifungal, anti-inflammatory, anticancer, anti-nociceptive and analgesic agent. In our earlier lab report, the methanolic extract of A.mexicana leaves posses anti-urolithiatic effects on pre-prepared calcium oxalate crystals by different In vitro assays such as nucleation assay, microscopic observation and aggregation assay. The research paper concluded that, Argemone mexicana leaves contained n-Hexadecanoic acid; cis,cis,cis-7,10,13-Hexadecatrienal; and 3,7,11,15-Tetramethyl-2-hexadecen-1-ol as major volatile constituents which will be used against various diseases. These result findings will help the society to find exact fit model of molecules through In silico approach in the drug discovery laboratory. Further the authors may be tested the efficacy of these compounds and non-volatile molecules from A.mexicana leaves in animal models against various diseases and disorders in future.